2018
DOI: 10.1111/jac.12323
|View full text |Cite
|
Sign up to set email alerts
|

Does post‐anthesis heat stress affect plant phenology, physiology, grain yield and protein content of durum wheat in a semi‐arid Mediterranean environment?

Abstract: Increasing air temperature due to changing climate is projected to decrease the length of the growing season, hasten vegetative development and maturation, and ultimately affect yield of many C3 crops. Previous multilocation trials highlighted strong relationships between thermal trends in the interval “beginning of flowering‐end of grain filling” and grain yield, and protein content in durum wheat (Triticum turgidum subsp. durum (Desf.) Husn.). With the aim to confirm these relationships, nine durum wheat gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
(52 reference statements)
4
15
0
Order By: Relevance
“…The grain NC was increased by HS in both hybrids without BR application. This result was consistent with studies on mature cereal crops [48,49]. The grain NC may have increased because the effect of HS on carbon/starch accumulation was more severe than that of nitrogen [49,50].…”
Section: Nitrogen Concentration In Stem Leaf and Grainsupporting
confidence: 91%
“…The grain NC was increased by HS in both hybrids without BR application. This result was consistent with studies on mature cereal crops [48,49]. The grain NC may have increased because the effect of HS on carbon/starch accumulation was more severe than that of nitrogen [49,50].…”
Section: Nitrogen Concentration In Stem Leaf and Grainsupporting
confidence: 91%
“…Creso in the second, and Svevo in the first year, both under conventional (12.7% and 12.6%), and Duilio under conventional and Claudio under no-chemical input in second year (10.7%) showed the significantly highest and lowest values overall. In general, protein content was slightly higher at the first year due probably to a warmer growing season; it has been shown that higher temperatures after anthesis favors higher rates of grain nitrogen accumulation, and/or lower rates of carbohydrate accumulation [9,[40][41][42]. Only Creso and Svevo presented almost one-point increase in protein content under conventional regimes.…”
Section: Quality Traitsmentioning
confidence: 96%
“…According to the increased importance of durum wheat along the cereal food/feed chains, a number of breeding programs have been implemented aiming at developing new genotypes and exploit old cultivars, including landraces [9]. The assessment of the breeding progress for durum wheat in Spain and in Italy during the 20th century pointed out that the advantages were similar to those of other semi-dwarf's spring wheat and consisted essentially in the reduction in plant height and harvest index increase, with an enhancement of source/sink [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The negative impacts of reproductive-stage water deficiency on grain number are predominantly linked to the decrease of photosynthetic activity, which causes insufficient source supply to the reproductive tissues, eventually leading to floret abortion and failed grain formation [ 9 , 18 ]. In Italian durum wheat cultivars, just a small increase in mean minimum air temperature post-anthesis caused grain yield reduction by up to 22.6% [ 19 ]. Significant genotypic differences in yield performance were observed between modern and traditional cultivars, mainly attributed to differences in their leaf traits, such as net photosynthesis rate and transpiration rate [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Italian durum wheat cultivars, just a small increase in mean minimum air temperature post-anthesis caused grain yield reduction by up to 22.6% [ 19 ]. Significant genotypic differences in yield performance were observed between modern and traditional cultivars, mainly attributed to differences in their leaf traits, such as net photosynthesis rate and transpiration rate [ 19 ]. Although water-deficit stress and high temperature are commonly coupled in the field, their combined effects can be quite different from their individual impact [ 1 , 8 ].…”
Section: Introductionmentioning
confidence: 99%